2017
DOI: 10.1063/1.4982798
|View full text |Cite
|
Sign up to set email alerts
|

Responsivity calibration of the extreme ultraviolet spectrometer in the range of 175-435 Å

Abstract: We reported the relative responsivity calibration of the grazing-incidence flat-field EUV spectrometer between 175 and 435 Å by means of two methods. The first method is implemented by measuring the diffraction efficiency of the grating with synchrotron radiation light source. Considering the transmission efficiency and quantum efficiency of the other optical components in the spectrometer, the total responsivity was then obtained. The second one was carried out by measuring line emissions from C3+, N4+ and O3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The spectral line at 257.262 Å (blend of MIT, E1 transition, and M2 transition) mentioned in Section 1, as well as the reference line at 226.31 Å, was measured with a resolving power of approximately 1000. The line intensity ratios 257/226 were calculated from the measurements and corrected with the grating efficiency, the CCD quantum efficiency, and the transmission efficiency of the aluminum filter in the grazingincidence flat-field spectrometer (Tu et al 2017a). It was found that the charge-state distributions of the trapped ions can be monitored by comparing the relative intensities between the Fe VIII 185.213 Å, Fe XI 188 Å, and Fe X lines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The spectral line at 257.262 Å (blend of MIT, E1 transition, and M2 transition) mentioned in Section 1, as well as the reference line at 226.31 Å, was measured with a resolving power of approximately 1000. The line intensity ratios 257/226 were calculated from the measurements and corrected with the grating efficiency, the CCD quantum efficiency, and the transmission efficiency of the aluminum filter in the grazingincidence flat-field spectrometer (Tu et al 2017a). It was found that the charge-state distributions of the trapped ions can be monitored by comparing the relative intensities between the Fe VIII 185.213 Å, Fe XI 188 Å, and Fe X lines.…”
Section: Resultsmentioning
confidence: 99%
“…On the measurement side, the ratios of line intensities depend on the accuracy of the grating efficiency, the CCD quantum efficiency, and the transmittance of the aluminum filter in front of the spectrometer. The efficiency calibration of the grating at a synchrotron light source was made three years ago (Tu et al 2017a) and applied to the efficiency values of the filter from its factory test a few years before. Although the wavelength range between 257.262 Å and 226.31 Å is not that large, it is still possible that the efficiency ratio at these two wavelengths will change over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The background, mainly due to the dark counts of the MCP, was estimated from the wavelength region where no line was observed, and subtracted. The correction on the relative quantum efficiency of the grating was made based on the data by Tu et al (2017). The correction was about 9 % in the largest case between the lines (a) and (d).…”
Section: Resonance In Fe 14+mentioning
confidence: 99%